2022
DOI: 10.1136/rmdopen-2022-002674
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and drug persistence of baricitinib monotherapy is similar to combination therapy in patients with active RA: a prospective observational study

Abstract: BackgroundBaricitinib (BARI) is approved for the treatment of rheumatoid arthritis (RA) after failure of conventional synthetic and biologic disease modifying anti-rheumatic drugs (cs/bDMARDs) in combination with methotrexate (MTX) or as monotherapy. However, real-world data are scarce regarding efficacy and drug persistence for BARI monotherapy (BARI-mono) versus its combination with MTX (BARI-combo).ObjectiveTo evaluate efficacy and drug persistence of BARImono compared with BARI-combo in routine clinical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…A small study from Spain has reported longer treatment persistence for first-line BARI compared with first-line TNFi (23). Other real-world data have also shown similar persistence for BARI monotherapy compared with BARI combination therapy (13). Finally, our findings are also compatible with real-world studies showing similar or slightly longer persistence for JAKi compared with TNFi (9)(10)(11).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A small study from Spain has reported longer treatment persistence for first-line BARI compared with first-line TNFi (23). Other real-world data have also shown similar persistence for BARI monotherapy compared with BARI combination therapy (13). Finally, our findings are also compatible with real-world studies showing similar or slightly longer persistence for JAKi compared with TNFi (9)(10)(11).…”
Section: Discussionsupporting
confidence: 89%
“…Data from a nationwide Swedish register have shown that patients on BARI have a similar or improved treatment response compared with TNFi or non‐TNFi biologic DMARDs (bDMARDs) ( 12 ). One single‐center study from Germany has shown similar drug persistence for BARI monotherapy compared with BARI received in combination with a conventional synthetic DMARD (csDMARD) ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Below is a comprehensive descriptive review of the literature regarding RWE for baricitinib that has been reported to date; data were sourced from registries, monocentric and multicentric clinical practice studies, administrative or insurance claim databases, or prospective observational studies. At the time of writing, 41 published sources for RWE of baricitinib in the treatment of RA were identified [ 29 , 33 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ].…”
Section: Baricitinib In Real-world Settingsmentioning
confidence: 99%
“…Supplementary Table S1 summarises available baseline characteristics of baricitinib-treated patients in real-world settings [ 29 , 33 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. The typical patient in the various RWE sources is aged about 60 years (which is older than the mean age of patients in baricitinib RCTs).…”
Section: Baricitinib In Real-world Settingsmentioning
confidence: 99%
“…In a 9.3-year study comparing baricitinib treatment as monotherapy or along with MTX, there was no difference in drug continuation at week 96 between monotherapy (62%) or MTX combination (56%). In this study, it was reported that 30.1% of patients were discontinued due to ineffectiveness and 8.6% due to side effects (14). In a study including 19 different country databases, JAKi users (41% baricitinib, 59% tofacitinib) were less likely to discontinue due to ineffectiveness and more likely to discontinue due to side effects compared with tumor necrosis factor inhibitor users (15).…”
Section: Efficacy Datamentioning
confidence: 78%